Professionalism of Islamic Religious Education Teachers in Building a Religious School Environment - Akmalludin; Amini; Taubatul Adzkiya; Sumaryati; Muslih Hidayat; Mohd Nasir (Universitas Pendidikan Ganesha, 2025)
The professionalism of Islamic Religious Education (PAI) teachers plays a crucial role in shaping students' religious character and creating a school environment grounded in religious values. In today's modern era, the challenges facing PAI teachers are increasingly complex, driven by technological advancements, globalization, and the declining morality of some students influenced by foreign cultures that are inconsistent with Islamic values. This situation demands that PAI teachers act not only as instructors delivering learning materials, but also as moral and spiritual role models capable of instilling Islamic values in every aspect of school life.This study aims to analyze how the professionalism of Islamic Religious Education (PAI) teachers is implemented in building a religious school environment and to identify its impact on student character development. The research problem stems from the weak integration of Islamic values within elementary school culture. This study used a qualitative approach with a case study design, conducted at SDIT.. The research subjects consisted of Islamic Religious Education (PAI) teachers, principals, and students who were selected purposively. Data were collected through in-depth interviews, participant observation, and documentation of religious activities. The results show that the professionalism of Islamic Religious Education (PAI) teachers, reflected in their commitment, discipline, and role model, play a significant role in internalizing Islamic values through their activities.neatQuran recitation, congregational prayer, and Friday almsgiving. These activities have been shown to improve students' discipline, empathy, and social responsibility. The implications of this research emphasize the importance of strengthening character-based teacher professional training to strengthen the school's religious culture.